2014
DOI: 10.1186/1477-7827-12-5
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale transcriptomics reveals differences among gonadal stages in Asian seabass (Lates calcarifer)

Abstract: BackgroundThe Asian seabass (Lates calcarifer) is a protandrous hermaphrodite that typically matures as a male at approximately 2–4 years of age and then changes sex in subsequent years. Although several sexual maturation stages have been described histologically for both testis and ovary, the underlying gene expression profiles remain lacking. The development of a gene expression platform is therefore necessary to improve our understanding of the gonad development of this cultured teleost species.MethodsThirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 89 publications
4
45
0
Order By: Relevance
“…Gene ontology terms of these differentially expressed genes included biological processes such as reproduction (GO:0000003), sexual reproduction (GO:0019953), the reproductive process (GO:0022414), the reproductive developmental process (GO:0003006), gamete generation (GO:0007276), fertilization (GO:0009566) and the reproductive cellular process (GO:0048610). Twenty-one of these transcripts were also shown to have sex-related roles or differential expression in the gonads in previous studies (Table 4) [8,[30][31][32][33][34]. This finding showed that the assembled transcriptome could be reliably used as a reference for differential expression analyses.…”
Section: Application Of the Asian Seabass Transcriptome For Rna-seq Ementioning
confidence: 54%
See 3 more Smart Citations
“…Gene ontology terms of these differentially expressed genes included biological processes such as reproduction (GO:0000003), sexual reproduction (GO:0019953), the reproductive process (GO:0022414), the reproductive developmental process (GO:0003006), gamete generation (GO:0007276), fertilization (GO:0009566) and the reproductive cellular process (GO:0048610). Twenty-one of these transcripts were also shown to have sex-related roles or differential expression in the gonads in previous studies (Table 4) [8,[30][31][32][33][34]. This finding showed that the assembled transcriptome could be reliably used as a reference for differential expression analyses.…”
Section: Application Of the Asian Seabass Transcriptome For Rna-seq Ementioning
confidence: 54%
“…Subsequently, the dataset was augmented by additional sequences in the form of pair-end reads generated on the Illumina HiSeq 2000 platform (Illumina Inc., San Diego, CA, USA) to provide sequence depth in order to improve the assembly. The 454 and SOLiD sequence data (incorporated and reassembled here) has been published and released previously [8]. The assembly from the initial round of Illumina HiSeq sequencing (HiSeq Round 1, HR1) was also utilized as part of a survey of repetitive elements in Asian seabass [7].…”
Section: Sample and Library Preparation Sequencing And Quality Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite an increasing availability of genetic resources for the species (e.g. microsatellite and SNP markers, linkage and BAC‐based maps and transcriptomic assemblies), the complete characterization of genes is still reliant on laborious molecular methods (e.g. genome walking/RACE PCR cloning/Sanger sequencing).…”
mentioning
confidence: 99%